Isoliquiritin Ameliorates Cisplatin-Induced Renal Proximal Tubular Cell Injury by Antagonizing Apoptosis, Oxidative Stress and Inflammation - Pei, Zhiyin; Wu, Meng; Yu, Hanqing; Long, Guangfeng; Gui, Zhen; Li, Xiaonan; Chen, Hongbing; Jia, Zhanjun; Xia, Weiwei (Frontiers in Medicine, 2022)
Acute kidney injury (AKI) is a clinical syndrome characterized by morbidity, mortality, and cost. Cis-diamminedichloroplatinum (cisplatin) is a chemotherapeutic agent used to treat solid tumors and hematological malignancies, but its side effects, especially nephrotoxicity, limit its clinical application. Isoliquiritin (ISL), one of the major flavonoid glycoside compounds in licorice, has been reported to have anti-apoptotic, antioxidant, and anti-inflammatory activities. However, the effect and mechanism of ISL on cisplatin-induced renal proximal tubular cell injury remain unknown. In this study, mouse proximal tubular cells (mPTCs) and human proximal tubule epithelial cells (HK2) were administered increasing concentrations of ISL from 7.8125 to 250 μM. Moreover, mPTC and HK2 cells were pretreated with ISL for 6-8 h, followed by stimulation with cisplatin for 24 h. CCK-8 assay was performed to evaluate the cell viability. Apoptosis and ROS of cells were measured by using flow cytometer and western blotting. Our results showed that ISL had no obvious effect on cell viability. ISL decreased cisplatin-induced cell injury in a dose-dependent manner. ISL also protected against cisplatin-induced cell apoptosis. Meanwhile, the enhanced protein levels of Bax, cleaved caspase-3/caspase-3 ratio, levels of Pp-65/p-65, levels of IL-6, and the production of reactive oxygen species (ROS) induced by cisplatin were significantly attenuated by ISL treatment. Moreover, ISL markedly increased the protein levels of Bcl-2 and SOD2, which were reduced by cisplatin stimulation. These results showed that ISL ameliorated cisplatin-induced renal proximal tubular cell injury by antagonizing apoptosis, oxidative stress and inflammation.